Personality measures of "high" and "low" achievers in mathematics of selected third year students at the Caloocan High School - Basilia, Lily Dolores Labrague 1932- (s.n.], 1965)
This study identifies the personality measures of "high" and "low" achievers in mathematics of selected third year students in Caloocan High School. These measures were then related to their achievement.